Lembar Kerja Peserta Didik (LKPD) Berwawasan Green Chemistry Untuk Meningkatkan Kemampuan Literasi Sains Pada Materi Asam Basa - Ulandari, Amalia; Mitarlis, Mitarlis (Universitas Negeri Semarang, 2021)
Science literacy and green chemistry is very needed in learning chemistry. The learning process uses student worksheet to increase scientific literacy ability and the application of green chemistry. The study aims to describe the feasibility of student worksheet with green chemistry insight to increase scientific literacy ability on the matter of acid base. The principles of green chemistry in this student worksheets were limited 3 principles. number 1 is preventing waste. number 5 is using safe solvent. and number 12 is minimizing the occurrencence of accidents. Research method was referred to the stage of 4-D development model (define, design, develop, and desseminate). This study is limited to the stage of development and limited test was conducted to 12 students in a state Senior High School. Analysis of the data uses quantitative descriptive methods. Feasibility in terms of validity, practicality, and effectiveness. Worksheet is stated to be valid, practical, and effective if the percentage results are obtained ≥ 61%. The result showed that the feasibility of student worksheets is reviewed from content validity a percentage of 91.67% and construct validity a percentage of 94.26% with very valid criteria. The practicality of student worksheets is reviewed from observation of student activities a percentage of 95% with very good interpretations and response of student a percentage of 95.09% with very practical interpretations. The effectiveness of the student worksheets reviewed from pretest and posttest of scientific literacy with N-gain score of 0.88 high category.